Invisible Influence : The Hidden Forces That Shape Behavior - Berger, Jonah (London Simon & Schuster, 2016)
From the New York Times bestselling author of Contagious, an exploration into the subtle, secret influences that effect the decisions we make, from what we buy, to the careers we choose.
Include Notes and Index
Keywords: Social influence -- Social choice -- Behavior modification